Determinants that Contributes to Stunting Prevention Behavior in Pregnant Woman in Indonesia - Nafiatus Sintya Deviatin; Alma Feriyanti; Shrimarti Rukmini Devy; Muji Sulistyowati; Leersia Yusi Ratnawati; Qurnia Andayani (Media Gizi Indonesia, 2022)
Stunting is a condition of growth and development failure that occurs in children due to chronic malnutrition from the first thousand days of life (1,000 HPK). Stunting Practical efforts in overcoming stunting can be made during pregnancy. The behavior of pregnant women will have an impact on the incidence of stunting in children. The objective of the study is to review determinants that contribute to the behavior of pregnant women in stunting prevention efforts in Indonesia. The design of this study used a literature review. The article studied in this study was published in the last five years and discusses the determinants that contribute to the behavior of pregnant women in efforts to prevent stunting. Article search using an electronic database, namely through Google Scholar, Garuda, and ScienceDirect. Several articles reviewed show that various determinants can contribute to stunting prevention behavior in pregnant women. In addition to maternal factors, physical and social-environmental factors also contribute to the conduct of pregnant women. These determinants can eventually become a challenge for the government to reduce stunting rates in Indonesia.